Doppler pulsatility index in spontaneous intracerebral hemorrhage - Kiphuth, Ines C.; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (European neurology, 2013)
Background and Purpose: Elevated intracranial pressure (ICP) as a result of intracerebral hemorrhage (ICH) and perihematomal edema often leads to tissue shift, which can be identified in cross-sectional imaging and presents a known predictor of functional outcome. Pulsatility indices (PIs) of the intracranial arteries as measured by transcranial Doppler sonography (TCD) may serve as surrogate parameters for ICP. This study aims to investigate whether PI correlates with ICP and midline shift and serves as a reliable predictor of functional outcome in patients with ICH. Methods: Within a 1-year period between April 2009 and April 2010, 136 patients with acute spontaneous, supratentorial ICH were admitted to our tertiary care hospital. One-hundred and twenty-four patients fulfilled the inclusion criteria and were eligible for analysis. TCD and transcranial duplex sonography were performed on admission and at least once more during hospital stay. Functional outcome was assessed 6 months after discharge. Correlation analyses, logistic regression analyses and receiver operating characteristic curves were calculated. Results: One-hundred and twenty-four patients were included in the analysis. Six-month mortality amounted to 39.5%. The ICH score and PIs of the middle cerebral artery were independent predictors of outcome 6 months after discharge. Conclusions: Early PI monitoring by TCD correlated with ICP and may be used to predict the outcome after 6 months. Copyright © 2013 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Functional outcome; Intracerebral hemorrhage; Midline shift; Pulsatility index; Transcranial duplex sonography